Life cycle assessment of greenhouse gas emissions and carbon mitigation methods in probiotic-fed broiler production - Chin, H.W.; Tee, T.P.; Tan, N.P.; Angkanaporn, Kris (CSIRO, 2024)
Context: Livestock production contributes significantly to global anthropogenic greenhouse gas emissions. Probiotic-fed broiler production has been shown to reduce greenhouse emissions in other nations significantly, however, outcomes in Malaysia are unknown. Aims: This study assesses the total greenhouse emissions of probiotic-fed broiler production from cradle to farm-gate using an accredited Life Cycle Assessment (LCA) tool, Greenhouse Accounting Framework (GAF). It determines the hotspot of greenhouse emissions and emission intensity of the farm in kg CO2-eq/kg liveweight. Three types of mitigation methods, i.e. selling untreated manure, composting, and conversion into biochar, were compared to identify their effectiveness. Methods: The research involves three broiler houses with one production cycle. Fifty-four gas samples and 90 poultry litter samples were collected throughout the production cycle and analysed for the targeted gases - i.e. carbon dioxide, methane, nitrogen and volatile solid composition. Analysis results were used to estimate total greenhouse emissions from the farm using the LCA-GAF model. The mitigation efficiency achieved by selling untreated manure, composting, and biochar production is assessed by estimating the carbon stock mass. Key results: A new LCA model based on probiotic-fed broiler production was generated, specifically using data obtained from the experiment. The experimental results indicated that energy consumption, i.e. electricity and fuel, have the highest greenhouse emissions (44%), followed by feed production with 40% of the total 53.51 t CO2-eq/house/cycle in the probiotic-fed broiler farm. The emissions intensity of the farm is 1.57 kg CO2-eq/kg liveweight. Estimates of the mitigation efficiency were compared among untreated manure, biochar, and compost. Conclusions: Energy consumption, particularly electricity and fuel, contributed the highest greenhouse emissions in the probiotic-fed broiler production. The strategy of selling untreated poultry litter was the most effective carbon mitigation method. However, due to its adverse environmental and human health impacts, converting poultry litter into biochar is the preferable mitigation option. Implications: This study is profound for the poultry industry and environmental sustainability. It highlights the crucial role of energy consumption in greenhouse emissions from the probiotic-fed broiler farm, and the necessity of addressing the environmental impacts. Implementing sustainable agricultural practices could lead to more ecological poultry production, contributing to global efforts in climate change mitigation.